MOLECULAR PROFILES OF ENDOMETRIAL HYPERPLASIA AND ENDOMETRIAL INTRAEPITHELIAL NEOPLASIA - S. A. Levakov; N. A. Sheshukova; A. G. Kedrova; A. S. Fedotova; E. A. Obukhova (Опухоли женской репродуктивной системы)
Objective: to assess molecular profiles of endometrial hyperplasia and endometrial intraepithelial neoplasia.Materials and methods. We conducted a retrospective study that included 77 patients with a morphologically verified hyperplastic process in the endometrium. Of them, 34 patients had endometrial hyperplasia and 33 patients had endometrial intraepithelial neoplasia. The control group comprised 30 women with no endometrial disorders according to the results of histological examination.Results. Patients with endometrial intraepithelial neoplasia are at high risk of developing cancer. High angiogenic activity, pronounced vascularization, and endometrial hypoxia are believed to be important risk factors contributing to tumor proliferation and transformation. The expression of inhibitors of apoptosis, such as survivin and Bcl-2, is usually increased in atypical cells, which may indicate their involvement in malignant transformation of cells and tumor invasive growth.Conclusion. Our findings confirm the important role of survivin and Bcl-2 in hyperplastic processes in the endometrium.